Tổng hợp hydrotalcit biến tính bằng stearat và ứng dụng trong lớp phủ epoxy - Xuân Hằng, Tô Thị; Dương, Nguyễn Thùy; Trúc, Trịnh Anh; Trước, Bùi Văn; Thu Trang, Nguyễn Thị; Thẩm, Đỗ Quang; Hoàng, Thái; Mai Thanh, Đinh Thị (Vietnam Journal of Chemistry, 2014)
Hydrotalcite–like compounds intercalated with stearate (HT-SA) were prepared using the coprecipitation method. The HT-SA obtained was characterized by infrared spectroscopy, X-ray diffraction and scanning electronic microscop (SEM). Epoxy coatings containing 3 % hydrotalcite were prepared and applied on carbon steel. The adhesion, impact resistance and flammability properties of epoxy coatings were evaluated. The obtained results show that stearate was intercalated in hydrotalcite. The presence of HT-SA improved the adhesion and flammability properties of epoxy coatings. Keywords: Hydrotalcite, epoxy coatings, stearate, flammability.